A retrospective study analyzing if lymph node ratio carbon nanoparticles predict stage III rectal cancer recurrence - Pi, Feng; Tang, Gang; Xie, Chaozheng; Cao, Yukun; Yang, Shilai; Wei, Zhengqiang (Frontiers in Oncology, 2023)
Background Lymph node ratio has garnered increasing attention as a prognostic marker for rectal cancer; however, few studies have investigated the relationship between lymph node ratio and rectal cancer recurrence. Additionally, Carbon Nanoparticle tracking is a safe and effective strategy for locating tumors and tracking lymph nodes. However, no studies have reported the relationship between Carbon Nanoparticles and rectal cancer recurrence. Methods Patients with stage III rectal cancer who underwent radical resection between January 2016 and 2020 were analyzed. The primary outcome was tumor recurrence. 269 patients with stage III rectal cancer were included in this study. The effects of lymph node ratio, Carbon Nanoparticles, and other clinicopathological factors on rectal cancer recurrence were assessed using univariate, multivariate analyses and the t-test. Results Univariate analysis determined tumor recurrence using cytokeratin 19 fragment, CA-199, CEA, N-stage, positive lymph nodes, total lymph nodes, and lymph node ratio(positive/total); with the lymph node ratio being the most relevant. Receiver operating characteristic (ROC) analysis determined lymph node ratio =0.38 as the optimal cutoff value. The analysis of lymph node ratio ≥0.38 and <0.38 showed statistical differences in three indicators: tumor recurrence, CEA, and use of Carbon Nanoparticles. Conclusion Lymph node ratio is a strong predictor of stage III rectal cancer recurrence and may be considered for inclusion in future tumor-node-metastasis staging and stage III rectal cancer stratification. In addition, we found that Carbon Nanoparticles use significantly increased total lymph nodes and decreased lymph node ratio.